2015
DOI: 10.1108/jic-02-2015-0014
|View full text |Cite
|
Sign up to set email alerts
|

IC and public sector: a structured literature review

Abstract: Purpose – The purpose of this paper is to present a structured literature review of the public sector intellectual capital (IC) literature. It is, in part, motivated by a recent review of the IC literature by Guthrie et al. (2012, p. 74), who found that the public sector is one of the least addressed areas of IC research. Design/methodology/approach – This paper presents a structured literature review of public sector IC articles that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 68 publications
1
98
0
4
Order By: Relevance
“…Similarly, Sotirakou and Zeppou (2004) and Abeysekera, Jebeile, and Kamuruddin (2010) also argue that public sector modernisation cannot work without the involvement and commitment of its human capital and thus IC is the most critical and valuable asset in developing new management systems in public sector organisations.To date, IC approach has mostly been applied to business sector (Guthrie, Ricceri, & Dumay, 2012). However, public sector organisations are also under continuous pressures to improve performance, which require more input in the form of human, structural and relational capital thus IC is assumed to play a huge role in the value creation process of this sector as well (Dumay, Guthrie, & Puntillo, 2015;Secundo, Dumay, Schiuma, & Passiante, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Sotirakou and Zeppou (2004) and Abeysekera, Jebeile, and Kamuruddin (2010) also argue that public sector modernisation cannot work without the involvement and commitment of its human capital and thus IC is the most critical and valuable asset in developing new management systems in public sector organisations.To date, IC approach has mostly been applied to business sector (Guthrie, Ricceri, & Dumay, 2012). However, public sector organisations are also under continuous pressures to improve performance, which require more input in the form of human, structural and relational capital thus IC is assumed to play a huge role in the value creation process of this sector as well (Dumay, Guthrie, & Puntillo, 2015;Secundo, Dumay, Schiuma, & Passiante, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The IC body of knowledge has evolved over a period of time from debates regarding its introduction, to its measurement, and to its practical implications in the organisations, to developing a broader IC eco-system of communities, regions, cities or organisations (Borin & Donato, 2015;Secundo, Lombardi, & Dumay, 2018). However, research is still needed regarding IC praxis in different contexts (Dumay & Garanina, 2013;Dumay, Guthrie & Puntillo, 2015;.…”
Section: Introductionmentioning
confidence: 99%
“…IC has attracted increasing attention from scholars and practitioners in the public sector in the last decade . However, it should be critically observed that studies regarding the measurement of disclosure of traditional IC components are still in their embryonic stage, especially with regard to local governments (Dumay, Guthrie, & Puntillo, 2015;Garlatti, Massaro, Dumay, & Zanin, 2014;Massaro et al, 2015). Thus, future research should focus on this under-investigated theme.…”
Section: External Reporting: Disclosure Of Non-financial Informationmentioning
confidence: 99%
“…We perform the critical analysis (Bryman and Bell, 2007;Moore and Parker, 2007) of the literature, focusing on intellectual capital of universities, by identifying the most significant papers published in the main stream journals and international conferences dedicated to intellectual capital and knowledge management by following insights from Dumay et al (2015). We studied these papers and reflected upon the instruments used by researchers to analyse and measure the intellectual capital of universities.…”
Section: Methodsologymentioning
confidence: 99%
“…It is made when considered in combination with altitude and latitude." The longitudinal dimension is also advocated by Chiucchi and Dumay (2015), and Dumay et al (2015), since intellectual capital should not be considered like a picture at a moment, but more like a journey. By introducing the idea of the nonlinear integrators, we answer the need of connectivity and interactions between the components of the intellectual capital (Dumay 2016;Skoog, 2003).…”
Section: The New Paradigm For Understanding Intellectual Capital Of Umentioning
confidence: 99%